STATEGI PEMILIHAN KOMPOSISI IKLAN UNTUK MENGUATKAN PESAN BAHASA PADA IKLAN SKINCARE DI TIKTOK - Dhania Aryu Liantika; Dewi Kusumaningsih; Wahyu Dini Septiari (Universitas Batanghari, 2023)
This study aims to explain the composition of the advertisements presented in the promotion of skin care advertisements on TikTok. This study uses a descriptive qualitative approach. Data source from videos on TikTok that contain advertisements for skin care products. The data studied are in the form of words, phrases, and sentences in the data source. Data sources are video advertisements for skin care products from the Skintific, Bioaqua, Npure, and Hada Labo brands on TikTok in the issues from June to July 2022. Data collection techniques are carried out in three ways, namely documentation techniques, observation techniques, and note-taking techniques. Search techniques by downloading advertisements for skin care products from TikTok and taking screenshots of the display on the screen. Then, the next technique is the observing and note-taking technique, which is listening to the results of all video recordings and recording the information contained in the research results. Data analysis was performed using an interactive analysis model, in three steps: 1) data reduction; 2) present (display) data; 3) draw conclusions. Analysis of the composition of the ad is carried out by looking at the parts of the ad composition which are divided into three parts, namely the main point, ad body and closing. The results showed that 90% of the total ads used the main item, 95% of the total ads used the ad body, and found 70% of the total ads used the closing section.